OMIC-05. PHOSPHOPROTEOMIC ANALYSIS IDENTIFIES SUBGROUP ENRICHED PATHWAYS AND KINASE SIGNATURES IN MEDULLOBLASTOMA. (1st June 2021) - Leskoske, Kristin; Garcia-Mansfield, Krystine; Krishnan, Aparna; Sharma, Ritin; Rusert, Jessica; Mesirov, Jill; Wechsler-Reya, Robert; Pirrotte, Patrick
Abstract: Medulloblastoma (MB) is classified into four molecular subgroups: wingless (WNT), sonic hedgehog (SHH), Group 3 (G3) and Group 4 (G4), each with different molecular profiles and patient outcomes. Subgroup heterogeneity and low mutational burdens have hindered the identification of actionable therapeutic targets, especially in G3 MB which has a particularly poor prognosis. Therefore, we took a (phospho)-proteomics approach to identify active pathways and potential therapeutic opportunities in twenty orthotopic patient-derived xenograft (PDX) models of MB comprising SHH, G3 and G4 subtypes. Through our enrichment analysis, we identified processes and pathways specifically upregulated in each MB subgroup. We also utilized neural network derived kinase-substrate predictions and kinase activity scores inferred by a heuristic machine learning algorithm to further characterize phosphosignaling activity. We found that MB PDX models recapitulate many features of primary MB tumors including two distinct proteomic subtypes of G3. G3a was enriched for transcription, translation and MYC target genes while G3b was enriched for axon guidance and neurotrophin signaling pathways. Notably, both G3a and G3b contained higher abundance of mitochondrial proteins, suggesting altered tumor metabolism in G3 MB. SHH PDXs displayed increased NFκB and JNK-MAPK signaling. Group 4 MBs most closely resembled differentiated neuronal cells and were enriched for PKC and AMPK signaling as well as DNA repair pathways. In conclusion, we have provided a comprehensive proteomic and phosphoproteomic characterization of commonly studied MB PDX models and revealed new insights into subgroup enriched pathways and kinase activity in MB.